Experimental investigation on the nonlinear dynamics of two mutually coupled 1550 nm multi-transverse-mode vertical-cavity surface-emitting lasers - Yang, Wenyan; Xia, Guangqiong; Jayaprasath, Elumalai; Jiang, Zaifu; Hou, Yushuang; Hu, Chunxia; Wu, Zhengmao (Applied optics. Optical technology and biomedical optics, 2019)
We experimentally investigate the nonlinear dynamics of two mutually coupled 1550 nm multi-transverse-mode vertical-cavity surface-emitting lasers (VCSELs). The results show that, through continuously varying the coupling coefficient, the -polarization fundamental transverse mode and the -polarization first-order transverse mode in both VCSELs can be driven into period one, period doubling, multi-period, and chaos states. When the two mutually coupled VCSELs are simultaneously operating in the periodic state, localized synchronizations between the corresponding modes are observed. Moreover, mappings of dynamical states for typical transverse modes of the two mutually coupled VCSELs in the parameter space of the frequency detuning and coupling coefficient are specified.